Polyphenol analysis and antioxidant activities of Cymbopogon citratus (DC) Stapf, leaves (Lemongrass) from different locations in the Philippines - Tan, Mae Joselle G.; Orejola, Joanna (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Cymbopogon citratus or "tanglad" (lemongrass) in Filipino is a perennial grass that has been intentionally introduced in the tropical and subtropical regions of the world for the essential oil and polyphenol contents from its leaves and is widely used as a culinary and medicinal herb. The limited data about the chemical profile of Cymbopogon citratus from different sources in the Philippines, with different methods of pre extraction treatment and extraction solvents were the main reasons for conducting this study. The relationship between antioxidant property and the phenolics profile of C. citratus from five different geographical locations within Luzon was explored. The results revealed that 80% methanol is better than water as solvent for extracting the phenolic compounds, flavonoids and produced extracts with higher antioxidant capacity. The extracts should be prepared from fresh samples rather than subjecting to air or oven drying for better yield of phenolic compounds and flavonoids, better antioxidant activity. Variation in phenolics and flavonoids content and antioxidant property were significant across sources. The antioxidant property of the plant showed a strong correlation to the total phenolics and total flavonoids. The results of this study provided foundation for establishing the total phenolics, total flavonoids and antioxidant property profile of C. citratus from Philippine sources. Hence, samples from other sources can further be explored to expand the data and build a better profile of the phenolics and antioxidant property of C. citratus. Investigation of optimum agronomic and environmental conditions is also warranted. To be able to have a more definitive chemical profile of the plant, TLC and HPLC methods can be optimized to provide complementary data for determination of the compounds responsible for the antioxidant property of C. citratus.
Thesis (Masters of Science in Pharmacy)--University of the Philippines Manila, January 2023.
Keywords: Polyphenols -- Analysis. -- Cymbopogon citratus -- Philippines; Antioxidants. -- Analysis -- Cymbopogon citratus -- Philippines; Cymbopogon citratus -- Leaves. -- Philippines